SP1-induced lncRNA TINCR overexpression contributes to colorectal cancer progression by sponging miR-7-5p - Yu, Shaojun (Aging (Albany NY), 2019)
Mounting evidences have indicated that long noncoding RNAs (lncRNAs) play pivotal roles in human diseases, especially in cancers. Recently, TINCR was proposed to be involved in tumor progression. However, its role in colorectal cancer (CRC) remains elusive. In our study, we found that SP1-induced TINCR was significantly upregulated in CRC tissues and cell lines. Moreover, cox multivariate survival analysis revealed that high TINCR was an independent predictor of poor overall survival (OS). Functionally, knockdown of TINCR obviously suppressed CRC cells proliferation, migration and invasion in vitro, and inhibited CRC cells growth and metastasis in vivo. Mechanistically, we identified TINCR could act as a miR-7-5p sponge using RNA pull down, luciferase reporter and RIP assays. Furthermore, we showed that TINCR might promote CRC progression via miR-7-5p-mediated PI3K/Akt/mTOR signaling pathway. Lastly, we revealed that plasma TINCR expression was upregulated in CRC when compared to healthy controls and could be a promising diagnostic biomarker for CRC. Based on above results, our data indicated that TINCR might serve as a potential diagnostic and prognostic biomarker for CRC.